Influence of Credit Restructuring on Company Financial Performance: Impact of PSAK 71 Implementation - Salsa Nabila Sholihati; Cahyaningsih Cahyaningsih (Postgraduate Program Merdeka University, 2024)
This study aims to analyze the differences in financial performance influenced by Allowance for Impairment Losses (CKPN), Capital Adequacy, and credit restructuring before and after the implementation of PSAK 71. This research employs a quantitative method with secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange from 2016 to 2023. The sample consists of 240 observations from 30 banks over eight years, selected thro-ugh purposive sampling. The analysis includes difference tests and panel data regression using E-views 12. The results indicate significant differences in CKPN, capital adequacy, credit restructuring, and financial performance before and after PSAK 71 implementation. These findings suggest that PSAK 71 significantly impacts financial performance and credit restructuring policies. CKPN and credit restructuring negatively affect financial performance, although not significantly, while capital adequacy positively affects financial performance, but not significantly. This study contributes to banking companies in decision-making related to accounting policies and credit restructuring, and provides investors with insights into factors affecting the financial performance of banks. JEL Classification: G21; G28; M41 DOI: https://doi.org/10.26905/afr.v7i3.13582